2013
DOI: 10.1111/jog.12070
|View full text |Cite
|
Sign up to set email alerts
|

Changes of maternal dietary intake, bodyweight and fetal growth throughout pregnancy in pregnant Japanese women

Abstract: Maternal bodyweight as well as eating habits established before pregnancy may have a considerable effect on fetal growth. There is an urgent need to improve the diet of Japanese women of child-bearing age, especially during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 19 publications
2
63
3
Order By: Relevance
“…The mean energy intake was significantly higher than previous studies [18,19]. However, consuming a large serving of rice and/or other starchy staple in all three main meals and the daily consumption of supplemental food with a higher energy value are central to this high energy intake.…”
Section: Discussionmentioning
confidence: 55%
“…The mean energy intake was significantly higher than previous studies [18,19]. However, consuming a large serving of rice and/or other starchy staple in all three main meals and the daily consumption of supplemental food with a higher energy value are central to this high energy intake.…”
Section: Discussionmentioning
confidence: 55%
“…It has been reported that an insufficient calorie intake during pregnancy leads to lower birth weight among Japanese infants [3]. However, it has been observed that a high energy ratio of fat intake during pregnancy in mice may cause hypertension and abnormal glucose tolerance, even if caloric intake is within recommended levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…LBWI are at higher risk of not only facing neonatal mortality and developmental delays but also of developing chronic diseases in adulthood, such as coronary heart disease, hypertension, and type 2 diabetes (developmental origin health and disease) [2]. Low body mass index (BMI) before pregnancy and low calorie intake during pregnancy is associated with lower birth weight [3]. Thus, the nutritional condition of pregnant Japanese women might have remained unchanged between 2005 and 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies are important, diet consists of a combination of meals, nutrients, and foods 5 , and is determined by social, dietary patterns 14 . This analytical procedure allows assessing a diet within a multidimensional context of exposure 6,10 by reducing the number of dietary variables, which are grouped into factors composed of correlated foods.…”
Section: Introductionmentioning
confidence: 99%